Distinctive Features of Remotely Concluded Contracts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the unique characteristics of remotely concluded contracts, which are rapidly developing today, and highlights their role in the contract system.